Arachne $1 (BVolume 05s - Ebers, Georg, 1837-1898; Safford, Mary J. (Mary Joanna), 1842-1916 (Salt Lake City, UT : Project Gutenberg, 2004)
"Arachne $1 (BVolume 05" by Georg Ebers is a historical novel set in Ancient Egypt, likely written in the late 19th century. The story centers around themes of artistic creation, personal tragedy, and dramatic interpersonal relationships, particularly focusing on the life of the blind sculptor Hermon and his struggles with love and despair following the loss of his sight and his dear friend Myrtilus. In this volume, Hermon grapples with the aftermath of a devastating fire that destroys his property and, alongside it, brings intense grief as he mourns the loss of his close friend. Confronted by doubt and despair, he finds himself contemplating suicide as he feels burdened by his blindness and the weight of his art lost. However, amidst the turmoil, there is a glimmer of hope as recognition for his work surfaces, and he learns of a substantial inheritance left to him by Myrtilus. This newfound wealth presents a path to navigate his future, drawing him back to society and the love of Daphne, a maiden who embodies the qualities of inspiration and resilience. The tale progresses with Hermon on a journey of self-discovery, as he learns to accept his circumstances and his love for Daphne amid the shadows of his past and present regrets. (This is an automatically generated summary.)s
Release date is 2004-04-01
This eBook was produced by David Widger
Keywords: Egypt -- History -- 332-30 B.C. -- Fiction; German fiction -- Translations into English